2006
DOI: 10.1111/j.1540-5414.2006.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiproduct, Multicriteria Model for Supplier Selection with Product Life‐Cycle Considerations

Abstract: In industrial purchasing contexts firms often procure a set of products from the same suppliers to benefit from economies of scale and scope. These products are often at different stages of their respective product life cycles (PLCs). Firms consider multiple criteria in purchasing such products, and the relative importance of these criteria varies depending on the PLC stage of a given product. Therefore, a firm should select suppliers and choose sourcing arrangements such that product requirements across multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(113 citation statements)
references
References 26 publications
0
109
0
Order By: Relevance
“…Under this definition, firms may purchase not only products themselves but also the services required to make these products marketable. Narasimhan et al (2006) reported that the strategic objectives of global outsourcing are different from those of traditional purchasing. Whereas traditional purchasing focuses on minimizing procurement costs, strategic global outsourcing considers quality, delivery, responsiveness and innovativeness in addition to costs.…”
Section: Global Outsourcingmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this definition, firms may purchase not only products themselves but also the services required to make these products marketable. Narasimhan et al (2006) reported that the strategic objectives of global outsourcing are different from those of traditional purchasing. Whereas traditional purchasing focuses on minimizing procurement costs, strategic global outsourcing considers quality, delivery, responsiveness and innovativeness in addition to costs.…”
Section: Global Outsourcingmentioning
confidence: 99%
“…Those criteria are delivery (geographic location, freight terms, trade restrictions and total order lead time), flexibility (capacity, inventory availability, information sharing, negotiability and customization), cost (supplier selling price, internal costs, ordering and invoicing), quality (continuous improvement programs, certification, customer service and the percentage of on-time shipments), reliability (feelings of trust, the national political situation, the status of the currency exchange and warranty policies). Narasimhan et al (2006) composed a model, for global supplier selection and order allocation and considered criteria such as direct product cost, the indirect cost of coordination, quality, delivery reliability and complexity of the supply base. Lin et al (2007) used infrastructure, country risk, government policy, human capital and cost when evaluating global suppliers.…”
Section: Outsourcing Decision Criteriamentioning
confidence: 99%
“…The AHP which was originally proposed by Saaty helps to reduce any multidimensional problem into one dimensional top down approach [14]. The application of AHP in current research work helps the decision makers to make pair-wise comparison between decision alternatives.…”
Section: B Selection Of Ahp Methodologymentioning
confidence: 99%
“…with respect to minimum and maximum order quantities. These goals were also used by Narasimhan et al (2006) in a multi-criteria mathematical programming supply chain model. We have lower and upper bound for x ij from both the vendor and the customer's point of view, as expressed in constraints (5)-(8).…”
Section: Mop Modelmentioning
confidence: 99%